2012
DOI: 10.1074/jbc.m112.373274
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of Translation Eukaryotic Initiation Factor 4E in Nucleophosmin 1 Haploinsufficient Cells Results in Changes in CCAAT Enhancer-binding Protein α Activity

Abstract: Background: Myeloid cell lines were generated from Npm1 ϩ/Ϫ mice to understand the role of NPM1 in MDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…For instance, eIF4E is a direct NF‐κB target which is dysregulated in M4/M5 AML . Other groups have shown that eIF4E is also a target of C/EBP . Furthermore, eIF4E mRNA stability is elevated by the HuR protein and is destabilized by AUF1 .…”
Section: Dysregulation Of Eif4e Levelsmentioning
confidence: 99%
“…For instance, eIF4E is a direct NF‐κB target which is dysregulated in M4/M5 AML . Other groups have shown that eIF4E is also a target of C/EBP . Furthermore, eIF4E mRNA stability is elevated by the HuR protein and is destabilized by AUF1 .…”
Section: Dysregulation Of Eif4e Levelsmentioning
confidence: 99%
“…Others acquire altered properties such as sodium permeability for the N‐terminally truncated form of the potassium channel, subfamily K, member 2 (K2P2.1), which changes neuron responsiveness in specific rat brain tissues and developmental stages . Alternative translation initiation can also cause a loss of function, such as the dominant negative effect of truncated CCAAT/enhancer binding protein beta (C/EBP β) , or can functionally modulate growth factors and oncogenes (including fibroblast growth factor (FGF) , vascular endothelial growth factor (VEGF) , and V‐myc avian myelocytomatosis viral oncogene homolog (c‐Myc) ). Moreover, N‐terminal proteoforms may have different cellular stabilities as is the case for the opioid receptor mu 1 (OPRM1) .…”
Section: Alternative Translation Increases the Complexity Of Eukaryotmentioning
confidence: 99%
“…The formation and function of the EIF4F complex need to be tightly regulated to maintain the cellular homeostasis. Some major signal transduction pathways (e.g., PI3K/Akt/mTOR or MAPK) [ 28 30 ] and transcription factors (e.g., MYC or C/EBPα) have been shown to regulate the EIF4F complex [ 31 , 32 ]. In NSCLC, the rapamycin mediated inhibition of mTOR signaling can increase the phosphorylation of both Akt and EIF4E through a negative feedback mechanism, while the PI3K inhibitors such as LY294002 can reverse such undesirable effects [ 33 ].…”
Section: Introductionmentioning
confidence: 99%